Single and Mixture Toxicity of Boron and Vanadium Nanoparticles in the Soil Annelid Enchytraeus crypticus: A Multi-Biomarker Approach - Ana Capitão; Joana Santos; Angela Barreto; Mónica J. B. Amorim; Vera L. Maria (Nanomaterials, 2022)
The increased use and production of new materials has contributed to Anthropocene biodiversity decrease. Therefore, a careful and effective toxicity evaluation of these new materials is crucial. However, environmental risk assessment is facing new challenges due to the specific characteristics of nanomaterials (NMs). Most of the available ecotoxicity studies target the aquatic ecosystems and single exposures of NMs. The present study evaluated Enchytraeus crypticus survival and reproduction (28 days) and biochemical responses (14 days) when exposed to nanoparticles of vanadium (VNPs) and boron (BNPs) (single and mixture; tested concentrations: 10 and 50 mg/kg). Although at the organism level the combined exposures (VNPs + BNPs) did not induce a different toxicity from the single exposures, the biochemical analysis revealed a more complex picture. VNPs presented a higher toxicity than BNPs. VNPs (50 mg/kg), independently of the presence of BNPs (additive or independent effects), caused a decrease in survival and reproduction. However, acetylcholinesterase, glutathione S-transferase, catalase, glutathione reductase activities, and lipid peroxidation levels revealed alterations in neurotoxicity, detoxification and antioxidant responses, depending on the time and type of exposure (single or mixture). The results from this study highlight different responses of the organisms to contaminants in single versus mixture exposures, mainly at the biochemical level.